Effects of taurine on metabolomics of bovine mammary epithelial cells under high temperature conditions - Liu, Feifei; Liang, Liang; Luo, Zonggang; Zhang, Gongwei; Zuo, Fuyuan; Wang, Ling (Frontiers in Veterinary Science, 2024)
High temperature induces heat stress, adversely affecting the growth and lactation performance of cows. Research has shown the protective effect of taurine against hepatotoxicity both in vivo and in vitro. This study aimed to investigate the effect of taurine on the metabolomics of mammary epithelial cells of dairy cows under high-temperature conditions. Mammary epithelial cells were exposed to 0 mmol/L (HS, control), 8 mmol/L (HT-8), and 32 mmol/L (HT-32) of taurine, then incubated at 42°C for 6 h. Metabolomics analysis was conducted using Liquid Chromatograph Mass Spectrometer (LC–MS). Compared with the HS group, 2,873 and 3,243 metabolites were detected in the HT-8 group in positive and negative ion modes. Among these, 108 and 97 metabolites were significantly upregulated in positive and negative ion modes, while 60 and 166 metabolites were downregulated. Notably, 15 different metabolites such as palmitic acid, adenine and hypoxanthine were screened out in the HT-8 group. Compared with the HS group, 2,873 and 3,243 metabolites were, respectively, detected in the HT-32 group in the positive and negative ion modes. Among those metabolites, 206 metabolites were significantly up-regulated, while 206 metabolites were significantly downregulated in the positive mode. On the other hand, 497 metabolites were significantly upregulated in the negative mode, while 517 metabolites were reported to be downregulated. Noteworthy, 30 distinct metabolites, such as palmitic acid, phytosphingosine, hypoxanthine, nonanoic acid, and octanoic acid, were screened out in the HT-32 group. KEGG enrichment analysis showed that these metabolites were mainly involved in lipid metabolism, purine metabolism and other biological processes. Overall, our study indicates that taurine supplementation alters the metabolites primarily associated with purine metabolism, lipid metabolism and other pathways to alleviate heat stress in bovine mammary epithelial cells.